Konflik Israel-Palestina: Bagaimana Seharusnya Gereja Bersikap? - Ragil Kristiawan (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
The prolonged conflict between Israel and Palestine has made statements by countries on it. Muslim-majority countries tend to support Palestine. On the other hand, Christian-majority countries will support Israel. This research seeks to find answers about how the church should expect this conflict. By using qualitative literature study methods, a single conclusion was produced that the church should be neutral in this conflict. The church's primary calling is not to get involved in the political feud between Israel and Palestine. Four main reasons why the church should be neutral about this conflict. First, Contemporary Israel is different from Israel in the OT in that they still reject Jesus Christ as the Messiah to this day. Second, there are often misinterpretations of Genesis 12:3, especially in terms of sending or cursing Israel and the blessings that accompany it. Third, righteousness elevates the status of the nation, but sin is a stain on the nation. Defending Israel or Palestine does not make the church full of God's blessings. Fourth, God really loves the nations. just as God loves Israel, so He loves Palestine. Praying for Israeli-Palestinian peace is the right step in accordance with God's heart.